A new reaction of P4S10 and Lawesson's reagent; a new method for the synthesis of dithieno[3,2-b;2′,3′-d]thiophenes - Ertas, E.; Ozturk, T. (Elsevier BV, 2004)
Abstract A new reaction of P 4 S 10 and Lawesson's reagent for the synthesis of fused thiophenes has been uncovered. It has given easy access to the synthesis of derivatives of the technologically important heterocycle dithieno[3,2- b ;2 ′ ,3 ′ - d ]thiophene, DTT. Electrochemical polymerization of one of the derivatives has been demonstrated.